Vitellogenin-2 Accumulation in the Fat Body and Hemolymph of Babesia-Infected Haemaphysalis longicornis Ticks - Kuniyori, Maki; Sato, Nariko; Yokoyama, Naoaki; Kawazu, Shin-ichiro; Xuan, Xuenan; Suzuki, Hiroshi; Fujisaki, Kozo; Umemiya-Shirafuji, Rika (Frontiers in Cellular and Infection Microbiology, 2022)
The protozoan parasite Babesia spp. invades into tick oocytes and remains in the offspring. The transovarial transmission phenomenon of Babesia in ticks has been demonstrated experimentally, but the molecular mechanisms remain unclear. Babesia invasion into oocytes occurs along with the progression of oogenesis. In the present study, to find the key tick factor(s) for Babesia transmission, we focused on molecules involved in yolk protein precursor (vitellogenin, Vg) synthesis and Vg uptake, which are crucial events in tick oogenesis. With a Haemaphysalis longicornis tick–Babesia ovata experimental model, the expression profiles of Akt, target of rapamycin, S6K, GATA, and Vg, Vg synthesis-related genes, and Vg receptor (VgR) and autophagy-related gene 6 (ATG6), Vg uptake-related genes, were analyzed using real-time PCR using tissues collected during the preovipositional period in Babesia-infected ticks. The expression levels of H. longicornis Vg-2 (HlVg-2) and HlVg-3 decreased in the fat body of Babesia-infected ticks 1 day after engorgement. In the ovary, HlVg-2 mRNA expression was significantly higher in Babesia-infected ticks than in uninfected ticks 1 and 2 days after engorgement and decreased 3 days after engorgement. HlVgR expression was significantly lower in Babesia-infected ticks than in uninfected ticks 2 and 4 days after engorgement. HlATG6 had a lower gene expression in Babesia-infected ticks compared to uninfected ticks 2 days after engorgement. Additionally, western blot analysis using protein extracts from each collected tissue revealed that H. longicornis Vg-2 (HlVg-2) accumulate in the fat body and hemolymph of Babesia-infected ticks. These results suggest that Vg uptake from the hemolymph to the ovary was suppressed in the presence of B. ovata. Moreover, HlVg-2 knockdown ticks had a lower detection rate of B. ovata DNA in the ovary and a significant reduction of B. ovata DNA in the hemolymph compared with control ticks. Taken together, our results suggest that accumulated HlVg-2 is associated with Babesia infection or transmission in the tick body. These findings, besides previous reports on VgR, provide important information to elucidate the transovarial transmission mechanisms of pathogens in tick vectors.